Hematological Indices May Be Useful in the Diagnosis of Systemic Lupus Erythematosus and in Determining Disease Activity in Behcet's Disease - Yolbas, Servet; Yildirim, Ahmet; Gozel, Nevzat; Uz, Burak; Koca, Suleyman Serdar (Karger, 2016)
Objectives: The aim of this study was to investigate the relationships between clinical features of rheumatic diseases and hematologic indices, including mean platelet volume (MPV), MPV/platelet ratio (MPR), platelet/lymphocyte ratio, and neutrophil/lymphocyte ratio (NLR). Subjects and Methods: Rheumatoid arthritis (RA; n = 91), systemic lupus erythematosus (SLE; n = 51), systemic sclerosis (SSc; n = 39), and Behcet's disease (BD; n = 53) patients, and 55 healthy controls (HC) were enrolled. Hematological indices were calculated and one-way analysis of variance, Mann-Whitney U and chi(2) tests, and receiver operating characteristic (ROC) analyses were performed. Results: The MPV and MPR were higher in the SLE group than the RA group (p < 0.05 and p < 0.01, respectively). ROC analysis indicated that MPV (area under the curve, AUC, 0.68, 95% CI 0.58-0.77) and MPR (AUC 0.69, 95% CI 0.59-0.78) were sensitive and specific markers for SLE against RA. The NLR was higher in the RA, SLE, and SSc groups compared to the HC group (p < 0.05, p < 0.001, and p < 0.01, respectively). The NLR was higher in the active BD patients than those that were inactive (p = 0.008). Besides, NLR was higher in patients with neuro-BD and patients with active genital ulcers compared to patients without neurological involvement (p < 0.01) and active genital ulcers (p < 0.05). Conclusion: The MPV and MPR were significantly higher in the SLE group than in the RA group. They were also higher in the active than in the inactive BD patients. The MPV and MPR are useful diagnostic tools for SLE, and NLR reflects disease activity in BD. However, further research should be performed to standardize these tools. (C) 2016 S. Karger AG, Basel
Keywords: Rheumatic diseases; Systemic lupus erythematosus; Behcet's disease; Hematological indices